ANALISIS STABILITAS TANAH SUBGRADE PADA PROYEK PEMBANGUNAN JALAN TOL JAKARTA-CIKAMPEK 2 SELATAN PAKET 3 - Yoan Hovandinata Sembiring; Doni Haidar Nur (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2023)
Subgrade soil is the foundation for pavements, both pavements on traffic lanes and shoulders. Thus, the subgrade is the final construction that receives the vehicle load distributed by the pavement. In simple cases, subgrade consists of natural soil without treatment; whereas in other, more common cases, subgrade consists of the original soil in the excavation or the top of the embankment which is compacted. As a land transportation infrastructure, pavement must have a surface that is always flat and rough, so that road users can feel comfortable and safe. Because it is built on subgrade soil, the pavement performance will be greatly influenced by the quality of the subgrade soil. The purpose of this paper is to determine whether the road foundation is sufficiently used with the existing soil, to carry out subgrade improvement and the use of geotextile and geogrid for subgrade improvement The data and information used are primary data from the Jakarta Cikampek 2 Selatan Paket 3 obtained from the results of soil tests in the field. The determination of the geotextile to be used is based on the results of the CBR test and the calculation of the load to be received by the geotextile and will also determine the type of geotextile to be used. The results obtained for the value of T = 23,951 Kn/m, then Geotextile Type GM-150 was used. By using non-woven geotextile as a separator at sta. 35+800 to 36+000 to avoid excessive replacement of soil layer thickness that does not meet specifications (soil with large compression properties), so that in terms of cost and implementation time it is more economical.